Some New Results on Bipolar-Valued Fuzzy d-Algebras - S. Praveena; M. Kamaraj (International Journal of Mathematics And its Applications, 2018)
In this paper we introduce definitions of generalized bipolar-valued fuzzy $d$-algebra and investigate some associate results.